Practical lessons learnt from the application of x-ray computed tomography to evaluate the internal structure of asphalt mixtures (2014)
X-ray Computed Tomography (X-ray CT) has allowed for the efficient non-destructive characterization of the internal structure of paving asphalt mixtures (AM), and has led to multiple practical lessons learnt based on the analysis of laboratory- and field-produced AM. This paper aims at summarizing these practical lessons, to facilitate their future application and further developments, in terms of: (i) fabrication of laboratory specimens, (ii) comparison of laboratory- and field-compacted mixtures, (iii) comparison of hot-mix asphalt and warm-mix asphalt mixtures, (iv) effects of additives, temperature, and compaction, (v) stone-on-stone contact, (vi) relationship between internal structure and performance, and (vii) modeling applications. These practical lessons are primarily gathered from the analysis of the air void distribution of laboratory-and field-produced AM, evaluated through X-ray CT, which has led to relevant inputs for the assessment of the response and performance of AM. X-ray CT enables computation of the AM internal structure with multiple practical applications and future opportunities to enhance the microstructure of AM and, consequently, optimize their performance.